Overgrazing on unmanaged grassland interfered with the restoration of adjacent grazing-banned grassland by affecting soil properties and microbial community - Fang, Mengchao; Lu, Guang; Zhang, Shuping; Liang, Wei (Frontiers in Microbiology, 2024)
A "grazing ban" policy has been implemented in some pastoral areas in China to fence degraded grasslands for restoration. However, fencing increased grazing pressures in unmanaged grasslands. Based on the mechanism of negative edge effect, we investigated whether overgrazing on unmanaged grassland interfered with the restoration of adjacent grazing-banned grassland by affecting soil properties and microbial community using a sample in Hulun Buir of Inner Mongolia, in order to optimize the "grazing ban" policy. Plant and soil were sampled in 30m away from the fence in unmanaged grassland (UM), the areas 30m (adjacent to UM) and 30-60m (not adjacent to UM) away from the fence in the grazingbanned grassland (F-30m and F-60m). The species richness and diversity of plant communities and the ASV number of fungal communities significantly decrease in F-30m and UM, and the simpson index of bacterial community significantly decreases in the F-30m, compared to F-60m. The abundance of fungi involved in soil organic matter decomposition significantly decrease, the abundance of stress-resistant bacteria significantly increase, while the abundance of bacteria involved in litter decomposition significantly decrease in UM and F-30m, compared to F-60m. The simplification of plant communities, decrease in soil water and total organic carbon contents can explain the variations of soil microbial communities in both UM and F-30m, compared to F-60m. The results of PLS-PM show that changes of plant community and soil microbial function guilds in UM may affect those in F-30m by changing soil water and total organic carbon contents. These results indicate that overgazing on unmanaged grassland interfered the restoration of adjacent grazing-banned grassland by affecting soil properties and microbial community. The grazing-banned grasslands should be adjusted periodically in order to avoid negative edge effect.